Antiviral activity of tenofovir alafenamide (TAF) against HIV‐1 clinical isolates harboring K65R. Issue 4 (18th April 2023) - Cox, Stephanie; Margot, Nicolas; Callebaut, Christian
Abstract: Tenofovir alafenamide (TAF) is a prodrug of the nucleoside reverse transcriptase (RT) inhibitor tenofovir (TFV). Compared to the earlier TFV prodrug, TFV disoproxil fumarate (TDF), TAF achieves more than fourfold‐higher intracellular levels of its active metabolite TFV diphosphate (TFV‐DP) in clinical studies, while achieving a significant reduction of TFV systemic exposure. Resistance to TFV has been well established, with the K65R mutation in RT as the signature mutation. Here we evaluated the in vitro activity of TAF and TDF in patient‐derived HIV‐1 isolates harboring the K65R mutation. Clinical isolates containing K65R were cloned into the pXXLAI construct ( n = 42). In vitro phenotypic susceptibility of the constructs to TAF and TDF was evaluated in an MT‐2 cell HIV assay and in viral breakthrough assays modeling physiological concentrations of TAF and TDF. TAF and TDF susceptibility were highly correlated in K65R‐containing mutants, ranging from 2.7‐ to 3.0‐fold (K65R alone) and 1.2‐ to 27.6‐fold (K65R+ other RT mutations) relative to wild‐type. In viral breakthrough assays mimicking differences in physiological concentrations, TAF inhibited breakthrough of 40 of 42 clinical isolates, while the TDF equivalent only inhibited 32 of 42 isolates tested. TAF displayed a higher barrier to resistance than TDF in this panel of K65R‐containing clinical isolates.